Pengaruh CAR, LDR, KAP dan NPL terhadap ROA Bank Go Public yang terdaftar di BEI - Grilseda, Nadya; Riyadi, Selamet (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Asset Quality (KAP), and Non Performing Loans (NPL) on Return On Assets (ROA) in Go Public Banking Companies listed in Indonesia Stock Exchange (BEI) 2015-2019. The population used in this study was 37 bank companies listed on the Indonesia Stock Exchange (IDX) before 2015. The data used is obtained from the financial statements of each bank through the official website of the Indonesia Stock Exchange (BEI). The sample selection used a purposive sampling technique through certain criteria in order to obtain a sample of 15 banks. Hypothesis testing uses panel data regression analysis using E-views 10 software. The results of the analysis show that partially, CAR, LDR, and NPL have a positive and insignificant effect on ROA, while KAP has a significant negative effect on ROA. However, simultaneously, CAR, LDR, KAP, and NPL have a significant effect on ROA.